Pengaruh Metode Aplikasi Pemupukan terhadap Pertumbuhan Bibit Kelapa Sawit Ramet dan Dami di Main Nursery - Silaen, Zefanya Timothy; Rohmiyati, Sri Manu; Noviana, Githa (Program Studi Agroteknologi INSTIPER, 2025)
ABSTRACT This research was conducted at PT. Kresna Duta Agroindo, specifically at the Pelakar Estate plantation in Sarolangun Village, Sarolangun Regency, Jambi Province, for six months, concurrent with an internship program. The study aimed to assess the impact of fertilizer application methods on the growth of oil palm seedlings of the Ramet and Dami Mas varieties in the Pelakar Estate main nursery. This study employed a completely randomized design (CRD) with two factors: variety and fertilizer application method. Two oil palm varieties were tested using two fertilizer application methods: a spoon and a practical fertilizer application tool (APP). Data from the observations were analyzed using analysis of variance (ANOVA) at a 5% significance level, and treatments that showed a significant effect were retested using Duncan's Multiple Range Test (DMRT). The analysis showed that the fertilizer application method, either using a spoon or an APP, had no effect on oil palm seedling growth parameters. Significant differences were observed in growth results between the different plant varieties. These findings indicate that the genetic factors of plant varieties have a greater influence on growth than the fertilizer application method.